2021
DOI: 10.3389/fphar.2021.635089
|View full text |Cite
|
Sign up to set email alerts
|

HIV Protease Inhibitors and Insulin Sensitivity: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Protease inhibitors (PIs) are believed to affect insulin sensitivity. We aimed to analyze the effect of PIs on insulin sensitivity and the onset of diabetes mellitus (DM) in patients with HIV.Methodology: We searched PubMed, Google Scholar, ClinicalTrals.gov, and the WHO International Clinical Trials Registry Platform till November 2020 for randomized controlled trials (RCTs) that studied the effects of PIs on insulin sensitivity and DM in patients with HIV. We followed the PRISMA and PICOS framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Currently, many developments have been made in terms of managing PLWH, especially through the use of ART to suppress or reduce the viral load ( 56 ). In fact, the published literature predominately reports on recent ART combinations, especially protease inhibitors or nucleoside reverse transcriptase inhibitors, which are potentially linked with the development of non-communicable diseases, including kidney disease-associated risk factors ( 57–59 ). Notably, the sustained use of a tenofovir disoproxil fumarate-containing ART regimen has been linked with the detrimental effects of oxidative stress and inflammation, driving pathological abnormalities in renal cells ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many developments have been made in terms of managing PLWH, especially through the use of ART to suppress or reduce the viral load ( 56 ). In fact, the published literature predominately reports on recent ART combinations, especially protease inhibitors or nucleoside reverse transcriptase inhibitors, which are potentially linked with the development of non-communicable diseases, including kidney disease-associated risk factors ( 57–59 ). Notably, the sustained use of a tenofovir disoproxil fumarate-containing ART regimen has been linked with the detrimental effects of oxidative stress and inflammation, driving pathological abnormalities in renal cells ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used. [16][17][18] We included studies that reported OBI in HIV participants in Africa. Diagnosis of OBI was laboratory-based in all studies.…”
Section: Methodsmentioning
confidence: 99%
“…Undetectable HVL does not mean HIV/AIDS cure rather it escapes killing by host immunity and ART medicines through establishing dormancy in reservoirs cells and tissues like lymphoid tissues [ 12 , 13 ]. When ART is stopped, HIV reservoirs replicate and increase in number, the phenomenon called viral rebound/ recrudescence .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proposed a substantial proportion of post-treatment people who do not experience a rebound after stopping ARV where others maintain undetectable without ART [ 13 , 14 ]. Nonetheless, ART remains to be the cornerstone of HIV so far [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%